2010
DOI: 10.1063/1.3430543
|View full text |Cite
|
Sign up to set email alerts
|

Structural defects working as active oxygen-reduction sites in partially oxidized Ta-carbonitride core-shell particles probed by using surface-sensitive conversion-electron-yield x-ray absorption spectroscopy

Abstract: We analyzed the local structure of the surface Ta-oxide phase of TaCN/Ta2O5 core-shell particles that have a high oxygen reduction activity by using surface-sensitive conversion-electron-yield x-ray absorption spectroscopy, suppressing the contribution from the TaCN cores. The radial structure analysis revealed that the catalytically-active Ta2O5 phase in the TaCN/Ta2O5 particle surface contains oxygen-vacancy defects with shorter Ta–O bonds leading to the slight expansion of the first Ta–O shell. Such oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 7 publications
0
44
0
Order By: Relevance
“…Also, Horowitz et al 21 has synthesized Pb 2 Ru 2 O 7-δ by co-precipitation of Pb(NO 3 ) 2 and Ru(NO 3 ) 2 and post heat-treatment, and identified δ as 0.5 ± 0.1 (heat-treatment temperature is uncertain). In comparison with those previous reports, the values of δ in this study were smaller.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Horowitz et al 21 has synthesized Pb 2 Ru 2 O 7-δ by co-precipitation of Pb(NO 3 ) 2 and Ru(NO 3 ) 2 and post heat-treatment, and identified δ as 0.5 ± 0.1 (heat-treatment temperature is uncertain). In comparison with those previous reports, the values of δ in this study were smaller.…”
Section: Resultsmentioning
confidence: 99%
“…However, in recent reports 2,8,9 about tantalum oxide-based ORR catalysts, it has been indicated that a surface oxygen vacancy behaves as an active site owing to its property of attracting oxygen molecule. Figure 9 is the plots of j S of Pb 2 Ru 2 O 7-δ heat-treated respective temperature as a function of δ, indicating that Pb 2 Ru 2 O 7-δ which contained more oxygen vacancies showed higher area specific activity.…”
Section: Discussion About Active Site For Orr and Effect Of Solution mentioning
confidence: 99%
“…We concluded that oxygen vacancies in the oxide particles acted as ORR active sites. 28,30 Carbon derived from phthalocyanine was deposited during the heat treatment and partially covered the zirconium oxides. The deposited carbon formed local electron conduction paths on the surface of the zirconium oxides.…”
mentioning
confidence: 99%
“…XAS was suitable for analyzing the catalytic properties of materials since it probes both structural and electronic structural information from the extended fine-structure (EXAFS) and near-edge structure (XANES), respectively. To obtain structural information of the surface phase, we used conversion-electron-yield (CEY) XAS in addition to the conventional transmission XAS [34]. Since the CEY-XAS detects the flux of He + ions produced by the electrons emitted from the near surface regions due to an Auger process, we can selectively analyze that local structure of near surface phases restricting the probing depth within the escape depth of the Auger electrons [35].…”
Section: Characterizationmentioning
confidence: 99%
“…The peaks at around 0.16, 0.30, and 0.35 nm were attributed to Nb-O, Nb-(O)-Nb(1) and Nb-(O)-Nb(2) coordination, respectively [45]. Although a complete determination of the local structure is difficult to obtain due to the Nyquist's theorem restriction, the difference in the radial structure functions could be explained by considering oxygen vacancies similar to Ta-CNO powders [34]. However, further experiments and detailed analyses should be required to identify the active sites.…”
Section: Structural and Electronic Propertiesmentioning
confidence: 99%